ICT trends that matter - Ahmad, Shamsatun Nahar (Universiti Teknologi MARA, Johor, 2025)
This book is a compilation of 14 thought-provoking chapters which discussed the most significant trends in Information and Communication Technology and their implications for education, industry and society.